ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI DEVIDEN PAYOUT RATIO DI BURSA EFEK JAKARTA TAHU 2001-2005 ( STUDI KASUS PERUSAHAAN MANUFAKTUR) - Edy Suryawardana (Universitas Semarang, 2010)
AbstractThe Investors decide their large alternatives Jnvestation influenced by several factors. Particulary the stock investations would influenced by stock market condition correlated with stock pricing. Based on 17 stock which analized with an index model, it gets 3 stock in the portofolio optimal composition. That compositions trap on the stock from another industries sector. The result of this research have some conclusion with deciding optimal portofolio based on the an Index Models.Key words : Cash Position, Current Ratio, Debt to Equity Ratio, Financial Leverage, Growth Potential, Return On Assets untuk diuji pengaruhnya terhadap Dividen Payout Ratio.